Pengaruh Activity Based Costing terhadap Peningkatan Kinerja Keuangan - Erni Suryandari F; Susanto Susanto; Muhammad Ali Aqsa (Universitas Muhammadiyah Yogyakarta, Indonesia, 2006)
This research was done to identify the influence of Activity-Based Costing toward the development of financial performance (Empirical Study in Stock Exchange of Jakarta). The respondents of this research are internal auditors in manufacturing companies whose names are registered in Indonesian Capital Market Directory in 2004. The obtained primary data in this research was from questionnaires that was sent to the respondents by using cross-sectional survey method. The data was processed by using Structural Equation Modeling (SEM) through goodness of fit index, confirmatory model and structural similarities experiments. The three tested factors in this research are ABC success, other initiative and enabler are listed in hypothesis that influence toward financial performance. The result of the research shows there is significant influence between ABC success toward the development of financial performance; on the other hand, other initiative and enablers don’t have significant influence toward the development of financial performance.